2019
DOI: 10.1088/1742-6596/1389/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Unidirectional motion of magnetic domain walls: the experiment and numerical simulation

Abstract: The results of study of unidirectional motion of topologically different domain structures under the influence of periodic bipolar and unipolar magnetic field pulses applied perpendicular to the sample plane of (111) iron garnet single crystal plate are presented. The response of the domain structure to the field pulses was studied by direct observations utilizing the stroboscopic technique. Experimentally obtained dependences of the speed of unidirectional motion of stripe domains on the parameters of externa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…In the frequency spectra of the evolutionary stellar models with a mass of 1.8 M , Pamyatnykh (2000) and Dupret et al (2005) have reported the presence of low order unstable radial modes where consecutive modes are separated with almost an equivalent distance in frequency Fig. 1 of Pamyatnykh 2000 andDupret et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the frequency spectra of the evolutionary stellar models with a mass of 1.8 M , Pamyatnykh (2000) and Dupret et al (2005) have reported the presence of low order unstable radial modes where consecutive modes are separated with almost an equivalent distance in frequency Fig. 1 of Pamyatnykh 2000 andDupret et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In the frequency spectra of the evolutionary stellar models with a mass of 1.8 M ⊙ , Pamyatnykh (2000) and Dupret et al (2005) have reported the presence of low order unstable radial modes where consecutive modes are separated with almost an equivalent distance in frequency (e.g., Fig. 1 of Pamyatnykh 2000 andDupret et al 2005).…”
Section: Discussionmentioning
confidence: 99%
“…F-type stars can show four types of pulsations: (i) δ Scutitype p-modes driven by the κ-mechanism acting in the He ii ionisation zone (Pamyatnykh et al 2000), (ii) γ Doradus-type g-modes that are caused by the convective flux blocking mechanism (Guzik et al 2000), (iii) gravito-inertial modes or Rossby (r) modes where the Coriolis force is the restoring force (Saio et al 2018), and (iv) stochastic solar-like oscillations for which pressure is the restoring force (e.g. Kjeldsen & Bedding 1995).…”
Section: Introductionmentioning
confidence: 99%